MicroRNAs in Neurotoxicity - Prameet Kaur; Arunmozhiarasi Armugam; Kandiah Jeyaseelan (Journal of Toxicology)
MicroRNAs are gaining importance as regulators of gene expression with the capability to fine-tune and modulate cellular events. The complex network with their selective targets (mRNAs/genes) pave way for regulation of many physiological processes. Dysregulation of normal neuronal activities could result in accumulation of substances that are detrimental to neuronal functions and subsequently result in neurotoxicity. Neurotoxicity-mediated pathophysiological conditions could then manifest as diseases or disabilities like Parkinson’s and Alzheimer’s which have debilitating implications. Such toxicity can be a result of individuals predisposed due to genetic inheritance or from other sources such as brain tumours. Neurotoxicity can also be brought about by external agents like drugs and alcohol as well as brain injury with miRNAs playing a pivotal role in diseases. It is therefore vital to understand the expression of these microRNAs and their impact on neuronal activities. In this paper, we discuss some of the neuronal pathophysiological conditions that could be caused by dysregulated microRNAs.